THE INFLUENCE OF COMPETENCE, DISCIPLINE OF VILLAGE APPARATUS AND LEADERSHIP STYLE ON THE EFFECTIVENESS OF SERVICESAT THE AMAR SAKTI VILLAGE OFFICE - Fitrina Afrianti; Ferry Siswadhi; Anggia Ayu Lestari; Genna Diola Handani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to determine the Influence of Competence, Village Apparatus Discipline and Leadership Style on Service Effectiveness Partially and simultaneously. The object of this study is the Amar Sakti Village Office, the respondents in this study are staff and village people who are 17 years old and above. The number of respondents in this study is 80 respondents. Based on the results of the previous analysis and discussion, it can be concluded as follows: Competency does not have a significant effect on Service Effectiveness at the Amar Sakti Village Office, this is evidenced by the calculation of the table < t (1.561 < 1.99167), Discipline has a significant effect on the Effectiveness of Service at the Amar Sakti Village Office, this is evidenced by t calculation > t table (3.406 > 1.99167), Leadership Style has a significant effect on Service Effectiveness at the Amar Sakti Village Office, this is evidenced by t calculation of > t table (4.959 > 1.99167).